(untitled) (Research, Society and Development, 2021)
There is no doubt of the benefits brought by the practice of physical exercises in the promotion of health, but the use of combined capacities in a same session is still contradictory. The aim of the present study was to verify the influence of a 10- week program of concurrent training on body composition and strength in adult women comparing it to programs of strength and aerobic activities. Thirty women were selected with minimum age of 55 years, randomized in four groups: group A1 (aerobic activity following by strength training), group F1 (strength training followed by aerobic activity), group A (aerobic training), group F (strength training). The body fat showed differences among the groups, the group F was significantly lower than A and A1; when strength was analyzed the results demonstrated differences in the lumbar area in the group A1 and in the strength of inferior members in A, A1 and F from pre- to post-test. Based on the data, we conclude that excepting of body composition, there is no variance in the analyzed variables in this group of women according to the type of training performed.